Interactive E-book Peat Ecosystem on Science Learning in Junior High School (Journal of Innovative Science Education, 2022)
Science learning on global warming and climate change integrated with Socio Scientific Issues of peat ecosystems is needed to increase students' knowledge of the environment. Learning uses interactive e-books that contain material in the form of text, images, and videos. This study aims to determine: (1) Validation of media and material experts; (2) Teacher's response; (3) Student response. The research subjects were two science teachers and ten seventh-grade students at SMPN 5 Palangka Raya, Central Kalimantan. The validity based on material and media experts is 91.2% on average, with very good criteria. The teacher's response to interactive e-books is in the 86.25% category with very good criteria. The average student response to interactive e-books is 78%, with a very good criteria—interactive e-book Valid and effective interactive e-book used in science learning.